Pengaruh Gratis Ongkir Dan Sistem Pembayaran Cash On Delivery-Cek Dulu (COD-Cek Dulu) Terhadap Minat Beli Pada E-Commerce Shopee - Wilda Julianti; Andang Fazri; Husni Hasbullah (Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2024)
This research is the result of quantitative research which aims to answer questions about the influence of free shipping and the COD-Cek Dulu payment system on buying interest in Shopee e-commerce. The population in this study are Shopee e-commerce users. The research methodology used is quantitative research and the sampling technique uses the snowball sampling method with a sample size of 96 respondents. The data collection technique uses a questionnaire with the help of a Google form which is processed using SPSS version 26 and the data analysis technique uses multiple linear regression.